Spontaneous Resolution of Congenital Dural Venous Sinus Ectasia Associated With Polymicrogyria—Case Report - Kozłowska, Zuzanna; Komasińska, Paulina; Steinborn, Barbara; Toboła-Wróbel, Kinga; Pietryga, Marek; Szymankiewicz-Breborowicz, Marta; Szczapa, Tomasz; Bekiesińska-Figatowska, Monika (Frontiers in Pediatrics, 2022)
Dural venous sinus ectasia belongs to a rare group of venous sinuses malformations of unknown origin and uncertain prognosis. We report the first patient with idiopathic congenital ectasia of the confluence of sinuses with thrombosis associated with bilateral polymicrogyria. It may highlight the causative relation between ischemia within central nervous system due to torcular herophili ectasia with thrombosis in early pregnancy and development of cortical malformations in neonates. We highlight also a role of MRI neuroimaging in diagnosis of these entities.